The aging male project (Faculty of Medicine Universitas Indonesia, 2001)
With an increasing life expectancy and a decreasing reproduction rate, the population structure changes. A Jenapharm R & D program investigates the endocrinology of aging men. In men, a decrease in production of sex steroids and other hormones with age can be observed. The typical patterns of daily rhythmicity become less distinct. This is part of a very complex picture in which not only isolated hormones are involved, but also the influence of hormones on each other. Many factors from the external and intemal environment mediated by neurotransmitters constantly affect the highly sensitive hormonal balance. Therefore, aging has also been defined as